Surveillance neuroimaging and neurologic examinations affect care for intracerebral hemorrhage - Maas, Matthew B. (Lippincott Williams & Wilkins, 2013)
OBJECTIVE: We tested the hypothesis that surveillance neuroimaging and neurologic examinations identified changes requiring emergent surgical interventions in patients with intracerebral hemorrhage (ICH). METHODS: Patients with primary ICH were enrolled into a prospective registry between December 2006 and July 2012. Patients were managed in a neuroscience intensive care unit with a protocol that included serial neuroimaging at 6, 24, and 48 hours, and hourly neurologic examinations using the Glasgow Coma Scale and NIH Stroke Scale. We evaluated all cases of craniotomy and ventriculostomy to determine whether the procedure was part of the initial management plan or occurred subsequently. For those that occurred subsequently, we determined whether worsening on neurologic examination or worsened neuroimaging findings initiated the process leading to intervention. RESULTS: There were 88 surgical interventions in 84 (35%) of the 239 patients studied, including ventriculostomy in 52 (59%), craniotomy in 21 (24%), and both in 11 (13%). Of the 88 interventions, 24 (27%) occurred subsequently and distinctly from initial management, a median of 15.9 hours (8.9–27.0 hours) after symptom onset. Thirteen (54%) were instigated by findings on neurologic examination and 11 (46%) by neuroimaging. Demographics, severity of hemorrhage, and hemorrhage location were not associated with delayed intervention. CONCLUSIONS: More than 25% of surgical interventions performed after ICH were prompted by delayed imaging or clinical findings. Serial neurologic examinations and neuroimaging are important and effective surveillance techniques for monitoring patients with ICH.